Empowerment of urban communities in utilizing small courtyards with hydroponic technology - Retno Wulandari; Francy Rivansuna Fifintari; Triwara Buddhisatyarini (Universitas Muhammadiyah Magelang, 2022)
Hydroponic technology is one way to grow crops on a small piece of land. Homes in urban areas can use this approach. The purpose of this community service is to increase the role of members of the Women Farmers Group (KWT) in the use of small urban yards using hydroponic technology, especially for KWT Agro 40 in Pilahan Village, Kotagede, Yogyakarta City. In this program, the empowerment of group members is achieved through counseling, training on demonstration plots, mentoring, oversight, and evaluation. Members of KWT Agro 40 are knowledgeable and skilled in using their yard to grow vegetables using hydroponic methods, allowing them to use their yard to improve family nutrition and income. This community service resulted in one hydroponic installation with the NFT system (Nutrient Film Technique) and 5 hydroponic installations with the wick system. Hydroponics technology made with the NFT system is placed in the group garden, while for hydroponics with the wick system it is placed in the group garden and in the homes of KWT members. The harvest from this hydroponic technology can meet the needs of healthy and nutritious vegetables and can reduce family expenses.